Electronic publishing: The Turkish Online Journal of Educational Technology (TOJET) - Îşman, Aytekin; Dabaj, Fahme; Gümüş, Agah (My University, 2004)
The main goal of this study is to examine TOJET (The Turkish Online Journal of Educational Technology) in terms of concept, ethical values, goals, mission statement, publishing values, interest field, indexing, evaluation publishing activities, and visitor's profile. There are four parts of this presentation, starting by explaining the online journal and its benefits, continuing by the structure of TOJET, then talking about the effect s of the journal on the global education, and finally, the expected future of TOJET.